The accuracy and promise of personal breathalysers for research: Steps toward a cost-effective reliable measure of alcohol intoxication? - Riordan, Benjamin C (Digit Health, 2017)
OBJECTIVE: Technology is continuing to shape the way we collect health data, including data on alcohol use. A number of technologies are being developed to objectively measure intoxication ‘in the wild’ without relying on self-report; the most immediate solution may be the use of personal breathalysers. In this study, we aimed to determine whether a cost-effective personal breathalyser would perform in a similar manner to a device used for roadside breath testing. METHOD: We intercepted young adults (n = 337; 45% men) outside three concerts, administered 5-min interviews, and asked for breath samples on two devices (a personal breathalyser and a police-grade breathalyser). RESULTS: Participants reported having consumed an average of 7.3 standard drinks before the interview and had a mean Blood Alcohol Content of 0.077 g/dl on the police-grade device and 0.085 g/dl on the personal device. Difference scores suggested the personal breathalyser was more likely to over report Blood Alcohol Content (bias = 0.008 g/dl). CONCLUSION: Although the personal device was more likely to over report Blood Alcohol Content compared with the police-grade device, the results suggest that personal devices could be used as a measure of Blood Alcohol Content when collecting data outside of the lab.